SOCIAL ACTIVITY OF WOMEN OF UZBEKISTAN AT THE MODERN STAGE - Shahnoza Rustamaliyeva (Journals Park Publishing, 2023)
The article describes the social activity of Uzbek women in today's development period, their role in society and family, their rights and interests, and the problems they face in social life and family today.